2018
DOI: 10.4103/ccd.ccd_461_18
|View full text |Cite
|
Sign up to set email alerts
|

Childhood pemphigus vulgaris: Report of two cases with emphasis on diagnostic approach

Abstract: Childhood pemphigus vulgaris (CPV) is a rare entity with clinical features and management primarily similar to those of adults; diagnosis may be difficult due to clinical similarity to other disorders such as herpetic gingivostomatitis which is more prevalent in this age group. We report two cases of CPV with emphasis on diagnostic approach. While treating such patients, it is imperative to diagnose CPV in the early stages to prevent serious morbidity and to adjust drug dosage to minimize side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Pemphigus Vulgaris (PV) is an uncommon autoimmune blistering disease involving the skin and mucous membranes. 1,2 Most patients with PV have circulating autoantibodies against desmogleins 1 and 3, which are transmembrane proteins of the desmosomes. The clinical disorder is a consequence of the loss of cell adhesion, which occurs due to the attack on transmembrane proteins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pemphigus Vulgaris (PV) is an uncommon autoimmune blistering disease involving the skin and mucous membranes. 1,2 Most patients with PV have circulating autoantibodies against desmogleins 1 and 3, which are transmembrane proteins of the desmosomes. The clinical disorder is a consequence of the loss of cell adhesion, which occurs due to the attack on transmembrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…There is no difference between PV and CPV concerning the diagnostic tests because CPV has similar clinical, histological, and immunological features seen in PV in adults. 2,3 Among bullous diseases in childhood, CPV is the least frequent entity and thus can be misdiagnosed. 2 The differential diagnosis of CPV includes (i) hand-footmouth disease, (ii) oral candidiasis, (iii) acute herpetic gingivostomatitis, (iv) erythema multiforme, (v) Behcet's disease, (vi) lichen planus, and (vii) recurrent aphthous stomatitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 PV is rarely found in children. 8 PV usually occurs in patients between 40 to 60 years of age, with a higher incidence in men. 4 In this case, it was found that the patient was 31 years old, with a chief complaint of new blisters from almost the entire body for two days before the examination.…”
Section: Discussionmentioning
confidence: 99%